2016
DOI: 10.1371/journal.pone.0167676
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Functional Variant(s) that Explain the Low-Density Lipoprotein Receptor (LDLR) GWAS SNP rs6511720 Association with Lower LDL-C and Risk of CHD

Abstract: BackgroundThe Low-Density Lipoprotein Receptor (LDLR) SNP rs6511720 (G>T), located in intron-1 of the gene, has been identified in genome-wide association studies (GWAS) as being associated with lower plasma levels of LDL-C and a lower risk of coronary heart disease (CHD). Whether or not rs6511720 is itself functional or a marker for a functional variant elsewhere in the gene is not known.MethodsThe association of LDLR SNP rs6511720 with incidence of CHD and levels of LDL-C was determined by reference to CARDI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 60 publications
0
24
0
1
Order By: Relevance
“…Similar low frequencies in APOA5 and LDLR homozygotes mutant genes were reported by Lazzaretti et al [15] in a cross-sectional study among HIV-infected patients on ART in the Brazilians population. Genome-wide associations studies have identified LDL-R SNP rs6511720 (G>T), which is located in intron-1 of the gene, to be associated with lower plasma levels of LDL-C and a lower risk of CHD [35]. Data from the GLGC consortium suggested that LDLR rs6511720 minor allele is prevalent in about 10% of the population and have established that the allele is protective, being associated with lower levels of LDL-C [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar low frequencies in APOA5 and LDLR homozygotes mutant genes were reported by Lazzaretti et al [15] in a cross-sectional study among HIV-infected patients on ART in the Brazilians population. Genome-wide associations studies have identified LDL-R SNP rs6511720 (G>T), which is located in intron-1 of the gene, to be associated with lower plasma levels of LDL-C and a lower risk of CHD [35]. Data from the GLGC consortium suggested that LDLR rs6511720 minor allele is prevalent in about 10% of the population and have established that the allele is protective, being associated with lower levels of LDL-C [46].…”
Section: Discussionmentioning
confidence: 99%
“…The four candidate SNPs (rs2066714, rs6511720, rs662799, and rs10892151) selected for this study have been shown in previous studies to be significantly associated with lipid serum abnormalities following a review of GWAS and PubMed reports of SNPs associated with dyslipidemia among HIV-infected individuals [24,[33][34][35]. Genomic DNA was isolated from EDTA-collected whole blood samples of study participants using the Qiagen midi kit prep as per manufacturer's protocol.…”
Section: Single Nucleotide Polymorphisms Selection and Genotypingmentioning
confidence: 99%
“…Concerning unaffected individuals with high GRS in quartile IV (II-16 and III-10 in family HC126, III-1 in family HC218, and II-3 in family HC806), the presence of an unknown factor can reduce the effect of the high GRS and explain the normal LDL-C levels. It can be: (1) an LDL-C-lowering variant in the APOB gene which abolish the hypercholesterolemia phenotype since we have not sequenced the whole gene [21], (2) the combined impact of several LDL-C-lowering SNPs such as rs6511720 and rs57217136 located in intron 1 of the LDLR [22] and rs11591147 (p.(Arg46Leu)) in PCSK9 [23] that have been reported to be associated with lower levels of LDL-C, (3) loss-of-function mutations in ANGPTL3 [21], or (4) environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…The SNP is in complete linkage disequilibrium with three intron-1 SNPs (rs141787760, rs60173709, rs57217136), so only one or more than one of these variants may be the functional SNP at this locus. Using luciferase reporter assays in the hepatoma cell line Huh7 cells we showed [51] that the rare alleles of both rs6511720 and rs57217136 (but not rs60173709) caused a significant increase in LDLR expression compared to the common alleles (+29% and +24%, respectively).…”
Section: Five Year Viewmentioning
confidence: 95%